A descriptive case series of necrotising enterocolitis; occurrence at Aga Khan University Hospital - Mumtaz Hashmi, Hina; Afroze, Bushra; Ariff, Shabina; Faisal Saleem, Ali (Journal of the Pakistan Medical Association, 2022)
The objective of this study was to determine the frequency and outcome of preterm infants diagnosed with Necrotising Enterocolitis (NEC). In a case series, 320 preterm infants were enrolled during a period of 12 months at Aga Khan University Hospital, Karachi, a tertiary care hospital. Diagnosis and staging was done as per Bell’s staging criteria. Possible confounders were filtered. Analysis was based on the form of treatment and symptom progression. During the study, NEC was observed in 29(9.06%) babies of which stages I, II and III were 69%, 24% and 7%, respectively. Outcome analysis showed that among the 29 neonates diagnosed with NEC, 23 were discharged and 6 expired. A 9% prevalence observed during the study suggests this to be to be a major challenge in neonatology. Mortality outcome of 21% diagnosed with NEC recommends an early diagnosis coupled with prompt and appropriate treatment and preventive measures to reduce the burden of NEC in future. Keywords: Prematurity, Bell’s Staging, Necrotising Enterocolitis.